Evaluation of the Weightage on Dermatological Pharmacotherapy in Undergraduate Pharmacology Education of Bangladesh (IAHS Medical Journal, 2023)
Background: The aim of pharmacology education is to make graduate competent enough to prescribe safely and effectively. So it is expected that pharmacology education would incorporate all the important aspects of prescribing. Skin diseases are associated with a considerable disease burden in Bangladesh and mostly treated in primary care settings by junior doctors.Materials and methods: This descriptive cross-sectional study was conducted to analyze the undergraduate pharmacology curriculum and written question papers (SAQ) of MBBS curriculum of 07 different universities (Bangladesh University of Professionals, University of Dhaka, University of Chittagong, University of Rajshahi, Shahjalal University of Science and Technology, University of Science and Technology, Chittagong and Gono Bishwabidyalay) of Bangladesh in last 10 years (January 2010 to November 2019). The evaluation was conducted through searching certain key phrases.Results: In Pharmacology & Therapeutics portion of the MBBS curricula, there was not a single hour to teach dermatological pharmacotherapy. Highest presence of dermatological pharmacotherapy related question was observed in Bangladesh University of Professionals (BUP) followed by University of Rajshahi (RU).And statistically significant difference (p